Segregation of a haplotype encompassing FEB1 with genetic epilepsy with febrile seizures plus in a Colombian family (2013)
ABSTRACT: Febrile seizures and epilepsy are believed to be linked and some forms of epilepsy are associated with a history of febrile seizures (FS). Linkage analysis to seven known loci for FS and/or genetic epilepsy with febrile seizures plus (GEFS plus) was performed in a small Colombian family. Short tandem repeat (STR) markers were genotyped and two-point linkage analysis and haplotype reconstruction were conducted. A maximum LOD score of 0.75 at marker D8S533 for FEB1 at a recombination fraction ( ) of 0 and a segregating haplotype were identified. FEB1 was the first locus to be associated with FS and this is the second report to describe this association. Two genes in this region, CRH and DEPDC2, are good putative candidate genes that may play a role in FS and/or GEFS plus.